2015
DOI: 10.1159/000367787
|View full text |Cite
|
Sign up to set email alerts
|

Is the Measurement of Serum Ischemia-Modified Albumin the Best Test to Diagnose Ovarian Torsion?

Abstract: Aim: The aim of this study is to evaluate the diagnostic value of serum oxidative stress marker levels (ischemia-modified albumin, IMA; malondialdehyde, MDA) and total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) levels that occur in ovarian torsion and to determine the threshold value of these markers in the diagnosis of ovarian torsion. Methods: In this prospective case-control study, 34 women (the study group) with acute pelvic pain (20 with and 14 without ovarian to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
2
10
0
1
Order By: Relevance
“…Ovarian ischemia–reperfusion injury owing to twisting and subsequent release of the MCT is the main pathophysiological cause of torsion . Previous studies have investigated various inflammatory mechanisms that could be involved in this process, such as mean platelet volume or cytokine expression . In the present study, white blood cell, neutrophil, and lymphocyte counts were all markedly higher in the torsion group than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Ovarian ischemia–reperfusion injury owing to twisting and subsequent release of the MCT is the main pathophysiological cause of torsion . Previous studies have investigated various inflammatory mechanisms that could be involved in this process, such as mean platelet volume or cytokine expression . In the present study, white blood cell, neutrophil, and lymphocyte counts were all markedly higher in the torsion group than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Only IMA levels were able to discriminate the presence or absence of torsion. In patients operated due to ovarian torsion, the best IMA cut‐off value in the IMA characteristic curve was 0.7045 absorbance unit (ABSU) with sensitivity and specificity of 90 % and 92.31 %, respectively …”
Section: Discussionmentioning
confidence: 99%
“…[2,26,27] In one of those, serum levels of oxidative stress markers including IMA were found to be higher in patients with acute appendicitis than in healthy individuals. However, the authors found no correlation between the pathological extent of acute appendicitis and oxidative stress markers.…”
Section: Discussionmentioning
confidence: 91%